Conceptual Framework for Secure Cluster Management In Software Networks (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Software Defined Networks (SDN) is a new concept of network architecture that provides the separation of control plane (controller) and data plane (switches) in network devices. Hidden Markov Model (HMM) scheme is proposed for cluster management. The utilization of the bandwidth is an issue because of the extensibility of the control plane. The Control plane in SDN focuses on a centralized solution, where a single control entity has an overall view of the network. To meet the administration, the board necessities of large-scale network situations, the controls plane is regularly completed in the sort of distributed controller clusters, Cluster management technology monitors all sort of events and should keep up a reliable global network status, which usually leads to big data in SDNs. Cluster management technology monitors all types of events and must maintain a consistent global network status, which usually leads to big data in SDNs. Simultaneously, the cluster security is an open issue because of the programmable and dynamic features of SDNs.